Revitalization of the Beramih Tradition in Nanga Bunut: Implementing Islamic Values in Local Culture - Halijah, Siti; Hermansyah, Hermansyah; Tuah, Dilah bin (Ta'allum: Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to examine the revitalization process of the beramih tradition in Nanga Bunut as an implementation of Islamic values within local culture. The beramih tradition, which reflects a spirit of togetherness and mutual cooperation (gotong royong), has been declining due to the influence of modernization and increasing individualism. To address this challenge, a revitalization strategy is needed—namely, the reactivation of cultural practices that are nearing extinction by adapting them to the current socio-religious context. Methods –This research employs a qualitative method with an ethnographic approach. Data collection techniques include in-depth interviews, participatory observation, and document analysis, involving 12 informants consisting of community leaders, religious figures, and the younger generation. Findings – The results show that beramih is rich in Islamic values such as friendship (silaturahmi), solidarity, and social care, which strengthen the social cohesion of the community. Revitalization efforts are carried out through religion-based cultural education, youth involvement, and the active participation of traditional and religious leaders in redesigning beramih activities to be relevant to contemporary societal needs. Value – This study concludes that the revitalization of the beramih tradition not only preserves local cultural heritage but also reinforces the Islamic identity of the Nanga Bunut community amidst the currents of globalization.